Design, synthesis and biological evaluation of peptidyl-vinylaminophosphonates as novel cysteine protease inhibitors - Bhattacharya, Asish K.; Rana, Kalpeshkumar C. (Bioorganic & Medicinal Chemistry, 2011)
We report herein, design and synthesis of vinylaminophosphonates, a novel class of compounds as possible cysteine protease inhibitors. The synthesis of vinylaminophosphonates has been accomplished employing Tsuji-Trost reaction as a key step. The synthesized compounds were assayed against papain, a model cysteine protease and some of our synthesized compounds showed IC50 values in the range of 30-54 mu M thereby suggesting that these chemical entities thus could constitute an interesting template for the design of potential novel protease inhibitors. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Cysteine; Inhibitor design; Protease inhibitors; synthesis; Tsuji-Trost reaction; Vinylaminophosphonates

Direct glycosylation of unprotected and unactivated sugars using bismuth nitrate pentahydrate - Polanki, Innaiah K.; Kurma, Siva H.; Bhattacharya, Asish K. (Journal of Carbohydrate Chemistry, 2015)
Bi(NO3)(3), a low-cost, mild, and environmentally green catalyst, has been successfully utilized for Fischer glycosylation for the synthesis of alkyl/aryl glycopyranosides by reacting unprotected sugars, namely, D-glucose, L-rhamnose, D-galactose, D-arabinose, and N-acetyl-D-glucosamine with various alcohols in good to excellent yields. The glycosides were formed with high alpha-selectivity. Further, an expedient separation of alpha- and beta-glycosides using silver nitrate-impregnated silica gel flash liquid chromatography has been developed.
Keywords: Bismuth nitrate; carbohydrates; Fischer glycosylation; Flash chromatography; Separation

Diastereoselective synthesis of beta-ether derivatives of artemisinin, an antimalarial drug: the effect of nitrile on stereoselectivity - Chand, Hemender R.; Bhattacharya, Asish K. (Asian Journal of Organic Chemistry, 2016)
Malaria is a life-threatening disease affecting a major portion of the world's population with considerable loss of human life. Artemisinin, isolated from Artemisia annua, its oil- and water-soluble derivatives, and other known antimalarials are recommended for artemisinin combination therapy by the World Health Organization. We have established a method for the stereoselective synthesis of beta-ether derivatives of dihydroartemisinin in high yield and high diastereoselectivity. The reaction either in acetonitrile or dichloromethane/trichloroacetonitrile (6:1) mixtures at 0 degrees C or room temperature, respectively, furnished the antimalarial drugs artemether 3 or arteether 4 in high yield with a high diastereomeric ratio. The effect the nitrile has on the yield and stereoselectivity is mechanistically explained.
Keywords: antimalarials; arteethers; artemisinin; nitriles; trichloroacetimidates

Design and synthesis of eugenol/isoeugenol glycoconjugates and other analogues as antifungal agents against Aspergillus fumigatus - Goswami, Lakshmi; Gupta, Lovely; Paul, Sayantan; Vermani, Maansi; Vijayaraghavan, Pooja; Bhattacharya, Asish K. (RSC Medicinal Chemistry, 2022)
Glycoconjugates are biologically significant molecules as they tend to serve a wide range of intra- and extra-cellular processes depending on their size and complexity. The secondary metabolites of the plant Myristica fragrans, eugenol and isoeugenol, have shown antifungal activities (IC50 1900 mu M). Therefore, we envisioned that glycoconjugates based on these two scaffolds could prove to be potent antifungal agents. Triazole-containing compounds have shown prominent activities as antifungal agents. Based on this, we opined that a Cu(i) catalyzed click reaction could serve as the bridging tool between a eugenol/isoeugenol moiety and sugars to synthesize eugenol/isoeugenol based glycoconjugates. In our present work, we have coupled propargylated eugenol/isoeugenol and azido sugar to furnish eugenol/isoeugenol based glycoconjugates. In another approach, we have carried out hydroxylation of the double bond of eugenol and subsequent azidation of a primary alcohol followed by intramolecular coupling reactions leading to various other analogues. All the synthesized compounds were assayed against an opportunistic pathogenic fungus, Aspergillus fumigatus. Among the synthesized compounds, two analogues have exhibited significant antifungal activities with IC50 values of 5.42 and 9.39 mu M, respectively. The study suggested that these two analogues inhibit cell wall-associated melanin hydrophobicity along with the number of conidia. The synthesized compounds were found to be non-cytotoxic to an untransformed cell line.

Design and synthesis of 1,3-diynes as potent antifungal agents against aspergillus fumigatus - Goswami, Lakshmi; Gupta, Lovely; Paul, Sayantan; Vijayaraghavan, Pooja; Bhattacharya, Asish K. (ChemMedChem, 2023)
Eugenol and isoeugenol, secondary metabolites isolated from the plant Myristica fragrans have displayed antifungal activities against Aspergillus fumigatus (IC50 1900 mu M). Compounds having conjugated unsaturation have been of great use as antifungals i. e. amphotericin B, nystatin and terbinafine etc. Hence, in the present study, we have designed and synthesised 1,3-diynes by utilizing Glaser-Hay and Cadiot-Chodkiewicz coupling reactions to furnish possible antifungal agents. Synthesis of 1,6-diphenoxyhexa-2,4-diyne derivatives was achieved by Cu(I) catalysed coupling of propargylated eugenol, isoeugenol, guaiacol, vanillin and dihydrogenated eugenol or eugenol in good to excellent yields. All the synthesized compounds were evaluated against pathogenic fungus A. fumigatus. Among all the synthesized compounds, one of the compounds was found to be exhibiting promising antifungal activity with IC50 value of 7.75 mu M thereby suggesting that this type of scaffold could pave the way for developing new antifungal agents. The most active compound was found to be low cytotoxic when assayed against L-132 cancer cell line. Effect of the most active compound on ergosterol biosynthesis has also been studied. Also, the most active compound exhibited significant anti-biofilm activity although the concentration was found to be higher than its anti-fungal activity. Morphological changes in the biofilm were remarkable under confocal laser scanning microscopy.
Keywords: 1; 3-Diynes; Antifungal agents; Aspergillus fumigatus; Cadiot-Chodkiewicz; Glaser-Hay